Inequality; Empirical Study on Sulawesi Island Development - Sri Indriyani S. Dai; Husain Gani (Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar, 2022)
This study aims to analyze and determine how big the influence of economic growth, population growth, investment growth and the human development index on changes in income inequality in Sulawesi. The novelty of this study is to explore the interrelation of population, investment and human development index (HDI) variables on inequality that occurs in Sulawesi as a whole.The data used in this study is secondary data with the type of panel data, a combination of time series and cross sections from 2010-2020 and 6 provinces in Sulawesi. The method used is the Panel Vector Error Correction Model (PVECM). The results of this study indicate that (1) Changes in Economic Growth have no significant positive effect on changes in Income Inequality, meaning that any increase in changes in Economic Growth can increase changes in Income Inequality in Sulawesi. (2) changes in population have an insignificant negative effect on changes in income inequality, meaning that any increase in population changes can reduce changes in income inequality in Sulawesi. (3) changes in investment growth have a negative and significant effect on changes in income inequality, meaning that any increase in investment changes can reduce changes in income inequality in Sulawesi. (4) changes in HDI have a positive and significant effect on changes in income inequality, meaning that every increase in HDI changes can increase changes in Income Inequality in Sulawesi. (5) Dummy changes have a negative and significant effect on changes in income inequality, meaning that every increase in Dummy changes can reduce changes in Income Inequality in Sulawesi. The implication of this research is that the government needs to increase economic growth and control population growth followed by reducing income inequality, especially in the long term, the government is also expected to increase human resources by creating jobs, decent education and health in order to reduce the problem of inequality in the region. Local governments are expected to be able to formulate investment policies that are more inclusive and oriented towards reducing inequality in Sulawesi so as to create more equitable welfare.